Abundance assessment of Sulawesi Banded Swallowtail, Papilio gigon gigon and availability of resource plants in Bantimurung Bulusaraung National Park, South Sulawesi, Indonesia - TAUFIQ ISMAIL; RISMA ILLA MAULANY; PUTU OKA NGAKAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ismail T, Maulany RI, Ngakan PO. 2024. Abundance assessment of Sulawesi Banded Swallowtail Papilio gigon gigon and availability of resource plants in Bantimurung Bulusaraung National Park, South Sulawesi, Indonesia. Biodiversitas 25: 673-682. The Sulawesi Banded Swallowtail (Papilio gigon gigon Felder & Felder, 1864) is an endemic butterfly species of Sulawesi, Indonesia currently under threat from hunting and trade activities and habitat degradation. This study aims to examine the abundance of P. gigon gigon and resource plants' availability and to analyze the relationship between resource host and nectar plant density with the abundance of the butterfly species in Bantimurung Bulusaraung National Park, South Sulawesi, Indonesia. Data were collected using the line transect method in two habitat types: settlement and forest located in three observation sites (Bantimurung, Leang-leang, and Pattunuang). The data were analyzed with Spearman's correlation test. The results showed a significant positive correlation in Bantimurung between the host plant densities (r = 0.258; p = 0.010) and nectar plants (r = 0.211; p = 0.036) with the abundance of P. gigon gigon. In Pattunuang, the host plants had indicated an insignificant correlation (r = 0.061; p = 0.548) with the abundance of P. gigon gigon, and in contrast, the nectar plants showed a significant positive correlation (r = 0.487; p = 0.000). Only in Leang-leang the correlation between the abundance of P. gigon gigon showed no significant correlation with both host (r = 0.152; p = 0.132) and nectar plants (r = 0.041; p = 0.686). Differences between the observation areas were suspected to be influenced by human activities such as tourism and hunting. Therefore, management interventions by the national park are required to support the conservation of P. gigon gigon in the area.